Transsacadic Information and Corollary Discharge in Local Field Potentials of Macaque V1 - Paradiso, Michael A.; Akers-Campbell, Seth; Ruiz, Octavio; Niemeyer, James E.; Geman, Stuart; Loper, Jackson (Frontiers in Integrative Neuroscience, 2019)
Approximately three times per second, human visual perception is interrupted by a saccadic eye movement. In addition to taking the eyes to a new location, several lines of evidence suggest that the saccades play multiple roles in visual perception. Indeed, it may be crucial that visual processing is informed about movements of the eyes in order to analyze visual input distinctly and efficiently on each fixation and preserve stable visual perception of the world across saccades. A variety of studies has demonstrated that activity in multiple brain areas is modulated by saccades. The hypothesis tested here is that these signals carry significant information that could be used in visual processing. To test this hypothesis, local field potentials were simultaneously recorded from multiple electrodes in macaque primary visual cortex; support vector machines were used to classify the peri-saccadic LFPs. We find that LFPs in area V1 carry information that can be used to distinguish neural activity associated with fixations from saccades, precisely estimate the onset time of fixations, and reliably infer the directions of saccades. This information may be used by the brain in processes including visual stability, saccadic suppression, receptive field remapping, fixation amplification, and trans-saccadic visual perception.